2015
DOI: 10.1590/1678-457x.6585
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the extraction process of polyphenols from cashew apple agro-industrial residues

Abstract: The goal of this study was to determine the chemical composition of cashew apples agro-industrial residue and optimize the process of polyphenols extraction in this residue. The extraction process conditions were defined using a 2 4-1 fractional factorial experimental design using acetone and methanol as solvents. The independent variables were: time (30 to 90 min), temperature (30 to 50 °C), solvent concentrations (50% to 90%), agitation speed (100 to 300 rpm); the dependent variables were: total phenolic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
2
23
1
1
Order By: Relevance
“…The byproducts that are generated from the agro‐industrial processing of cashew apples comprise mainly mashed flesh and peels and represent approximately 20% of the apple total weight . Some studies have investigated these byproducts as a source of bioactive phytochemicals, particularly those with recognized antioxidant properties . Prebiotic components (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The byproducts that are generated from the agro‐industrial processing of cashew apples comprise mainly mashed flesh and peels and represent approximately 20% of the apple total weight . Some studies have investigated these byproducts as a source of bioactive phytochemicals, particularly those with recognized antioxidant properties . Prebiotic components (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Agro-industrial byproduct extracts have shown up as trend because they may represent a natural source of bioactive and biopreservatives compounds (Ayala-Zavala et al, 2011;Siqueira et al, 2013;Gyawali & Ibrahim, 2014;Andrade et al, 2015), representing a way of industrial waste management, also potentially reflecting on final product costs, due to their potential as low-cost source (Silveira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hydro-organic mixtures induce better swelling (Koffi et al, 2010) and increases porosity (Hismath et al, 2011) of the crushed material, influencing the extractability (Cheng et al, 2013) (Jensen et al, 2007), few inorganic salts and some polyphenols (Andrade et al, 2015).…”
Section: Resultsmentioning
confidence: 99%